2006
DOI: 10.1080/02640410500520559
|View full text |Cite
|
Sign up to set email alerts
|

The relative power output and relative lean body mass of World and Olympic male and female champions with implications for gender equity

Abstract: A uniform measure of the gender-related differential performance of female and male Olympic and World champions is proposed: relative power output applied to the environment. Laws of physics are employed to derive equations for estimating relative power output. In previous controlled laboratory studies, equally trained male and female athletes were shown to have a relative power output not significantly different from relative lean body mass. As to the estimated power output for 32 Olympic and World championsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 21 publications
4
28
1
1
Order By: Relevance
“…Within the general population, sexual dimorphism is readily observed in a range of gross (absolute) anthropometric variables, with males typically being taller and heavier as well as possessing more muscle but less fat mass than females (Lee et al, 2000;Sierra-Johnson, Johnson, Bailey, & Turner, 2004). Similar degrees of sexual dimorphism have also been observed in elite female and male divers (Carter & Ackland, 1998), volleyball players (Gualdi-Russo & Zaccagni, 2001), middle-distance runners (De Ridder, Smith, Wilders, & Underhay, 2003), swimmers (Coetzee, 2007), and mixed athletic populations (Drabik, 1988;Stefani, 2006). In addition, Carter and Ackland (1998) and Gualdi-Russo and Zaccagni (2001) reported inter-gender differences in body fat distribution patterns and found that females were less mesomorphic and more endomorphic than their male counterparts.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Within the general population, sexual dimorphism is readily observed in a range of gross (absolute) anthropometric variables, with males typically being taller and heavier as well as possessing more muscle but less fat mass than females (Lee et al, 2000;Sierra-Johnson, Johnson, Bailey, & Turner, 2004). Similar degrees of sexual dimorphism have also been observed in elite female and male divers (Carter & Ackland, 1998), volleyball players (Gualdi-Russo & Zaccagni, 2001), middle-distance runners (De Ridder, Smith, Wilders, & Underhay, 2003), swimmers (Coetzee, 2007), and mixed athletic populations (Drabik, 1988;Stefani, 2006). In addition, Carter and Ackland (1998) and Gualdi-Russo and Zaccagni (2001) reported inter-gender differences in body fat distribution patterns and found that females were less mesomorphic and more endomorphic than their male counterparts.…”
Section: Introductionmentioning
confidence: 81%
“…Overall, these results suggest that successful female and male athletes in the same sport have relatively similar proportional characteristics and that the inter-gender differences in absolute performance reflect differences in their absolute anthropometry (Stefani, 2006). Such findings suggest that if females are to perform at the same absolute standard as males, they may need to develop the same absolute anthropometric characteristics as their male counterparts.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast to relatively sedentary age-matched controls, talented female speed skaters showed no gradual fat increase in their adolescence [23]. The delivered external power per kilogram lean body weight did not differ between female and male skaters, despite the higher power outputs of male skaters [12,24]. Although most anthropometrical studies were conducted in the previous century, the more recent studies [16,21] suggest that anthropometry has not changed over time.…”
Section: Anthropometry Of Speed Skatersmentioning
confidence: 97%
“…This difference in body composition affects performance when the body is lifted against gravity, or when physiological values are related to body weight (18). Therefore, women have a lower power-to-total-weight ratio since power output is related to lean body mass (21).…”
Section: Introductionmentioning
confidence: 99%